Miniaturization of Microstrip Bandpass Filters Using Multilayer Configuration for Wideband Application - Adam, Helmi (2009)
This thesis presents new designs of wideband bandpass filter for X-band application using various resonator configurations in multilayer microstrip. Strong coupling required for wideband filter is realized by arranging multiple layers of microstrip lines on different dielectric substrates and overlapping these lines. For the first design, half wavelength coupled lines resonator is used to design wideband X-band bandpass filter, and the resonator is rotated to make the filter more compact. The measured passband return loss for this filter is better than -12.4 dB and the insertion loss is less than 2.5 dB. For second design, microstrip hairpin resonator is employed to build the miniaturized bandpass filter. Since adjacent hairpin resonator lines are placed at different levels, there are two possible ways to change coupling strength by varying the overlapping gap between two resonators; vertically and horizontally. Both have different benefit, one can reduce the filter length, and obtain symmetrical response. The other can reduce filter width, giving sharper rejection at high frequency. Both configurations produce very small and compact filter size, at 5.0 x 14.6 mm2 and 3.2 x 16.1 mm2 for the first and second proposed filter type respectively. The measured passband insertion loss for both filters are less than 2.3 dB and the passband return loss is better than -16 dB for the first filter type and -13 dB for the second filter type. Multilayer configuration gives freedom to choose any resonator shape and combine with another shape to make the filter in very compact size. For the last design in this thesis, hairpin resonator has been combined with half wavelength coupled lines resonator in multilayer configuration. Both different resonator shapes are placed on two different substrates with different dielectric constants, whereby the hairpin resonators are placed on the bottom layer and the straight line resonators are placed on the upper layer. The hybrid between hairpin resonator and half wavelength coupled lines configuration has made the filter even more compact and produce a very small filter size, only at 10 x 10 mm2. The measured passband return loss for this filter is better than -12.5 dB and the insertion loss is less than 2.3 dB. All of the filters are fabricated on 0.254 mm thickness R/T Duroid 6010 and R/T Duroid 5880 with dielectric constant 10.2 and 2.2 respectively using standard photolithography technique. Two layers of substrate are joined using epoxy adhesion which has dielectric constant of 3.6. This epoxy layer is included in simulation. Broader bandwidth produced by those filter configurations are proven able to cover the whole X-band frequencies of 44% bandwidth at 10.2 GHz center frequency with excellent Chebyshev responses. The measured results agree well with the simulated responses. The measured responses and group delay exhibit that all of designed filters have good performance.